Lithium Induced Amenorrhea: A First Case Report - KE, Balakumar; Tayal, Vandana; Egambarame, Vidhya; Roy, Vandana (Acta medica Lituanica, 2024)
A 19-year-old female, known case of bipolar disorder had history of amenorrhea (absence of menstruation) for three years. While other causes of amenorrhea such as CNS, pregnancy, other medications, and thyroid issues were ruled out, she was found to have hyper-prolactinemia. Although antipsychotic medications are known to cause amenorrhea due to dopamine receptor blockade, which may result in hyperprolactinemia, the patient’s symptoms began before she started these medications. Only drug that she was on for long period is lithium. Current literature shows mixed evidence about lithium’s impact on prolactin levels, which can affect menstruation. This case may represent the first report of lithium causing amenorrhea through elevated prolactin levels. Clinicians should be aware of this potential side effect and monitor patients accordingly. Further studies are needed to confirm and understand this potential link.